2017
DOI: 10.1371/journal.pone.0176638
|View full text |Cite
|
Sign up to set email alerts
|

Differential spontaneous recovery across cognitive abilities during detoxification period in alcohol-dependence

Abstract: ObjectiveThere is a lack of consensus regarding the extent to which cognitive dysfunctions may recover upon cessation of alcohol intake by alcohol-dependents (AD), and the divergent findings are most likely due to methodological differences between the various studies. The present study was aimed at conducting a very strict longitudinal study of cognitive recovery in terms of assessment points, the duration of abstinence, control of age and duration of the addiction, and by use of individual analyses in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 88 publications
1
29
0
3
Order By: Relevance
“…In den häufigen Behandlungsfällen der Intoxikation und des Entzuges findet zu Beginn der Behandlung in den ersten Stunden und Tagen oftmals eine erhebliche klinische Besserung statt, allerdings ohne durchgreifende Verbesserung der Grunderkrankung (Abhängigkeit) [16]. Somit bieten CGI und GAF die Möglichkeit, diese Besserung abzubilden, allerdings nicht die Remission von Eigenschaften der Abhängigkeitserkrankung, wie die verminderte Kontrolle über den Substanzkonsum oder das Auftreten von Suchtdruck (Craving).…”
Section: Alkoholbezogene Störungenunclassified
See 1 more Smart Citation
“…In den häufigen Behandlungsfällen der Intoxikation und des Entzuges findet zu Beginn der Behandlung in den ersten Stunden und Tagen oftmals eine erhebliche klinische Besserung statt, allerdings ohne durchgreifende Verbesserung der Grunderkrankung (Abhängigkeit) [16]. Somit bieten CGI und GAF die Möglichkeit, diese Besserung abzubilden, allerdings nicht die Remission von Eigenschaften der Abhängigkeitserkrankung, wie die verminderte Kontrolle über den Substanzkonsum oder das Auftreten von Suchtdruck (Craving).…”
Section: Alkoholbezogene Störungenunclassified
“…Wird die durchschnittliche Besserung beider Instrumente gegen die Aufenthaltsdauer aufgetragen, zeigen sich optimale Änderungen erst nach 3-4 Wochen stationärer Behandlung. Dies stützt die Hypothese, dass es sich bei ASUD um mutmaßlich schwer und komorbid kranke und beeinträchtigte Personen handelt, die einen längeren stationären Aufenthalt auch in der Akutbehandlung benötigen, um eine ausreichende Besserung für die ambulante oder rehabilitative Postakutbehandlung zu erreichen, möglicherweise weil die Personen sich hinsichtlich ihrer kognitiven Eigenschaften noch nicht ausreichend von den toxischen Effekten der jeweiligen Substanz und deren Entzug erholt haben [15,16]. Welchen Einfluss komorbide psychische und somatische Erkrankungen auf die Besserung und die Dauer des stationären Aufenthalts haben, kann möglicherweise in den Vitos-QI-Datensätzen der Folgejahre besser analysiert und beurteilt werden.…”
Section: Diskussionunclassified
“… 31 Longitudinal studies also found substantive differences in change trajectories across domains, supporting the general conclusions derived from cross-sectional comparisons of subgroups of people with AUD who differed in abstinence length. 4 Petit and colleagues 32 recently investigated the effects of abstinence on alcohol-related working memory and inhibitory control deficits. By the third week of abstinence, working memory function was indistinguishable between the AUD and control groups, whereas inhibitory control deficits remained.…”
Section: Effects Of Recoverymentioning
confidence: 99%
“…For instance, in alcohol use disorder, some patients fully recover from their cognitive impairments after alcohol detoxification, others still present neurocognitive impairments after 1 year of abstinence, and others may have permanent impairments [10]. In particular, one study stressed that after 2-3 weeks of alcohol detoxification, only half of the patients who exhibited impairments in working memory at the beginning of detoxification spontaneously recovered [20]. Cognitive remediation therapy studies have, however, largely ignored these interindividual differences.…”
Section: How Can the Efficacy Of Cognitive Remediation Therapy In Patmentioning
confidence: 99%